Reimagining careers in unpropitious creative fields through the meta-creativity of alternative creativity: implications for the music industry - Moxey, Lauren; Daniel, Ryan (Creativity Studies, 2023)
Work by Abraham Maslow and others has proposed that a reasonable degree of fulfilment of various human needs is required for an individual to experience positive wellbeing. Given that an individual’s occupation provides vital financial, social, emotional, and cognitive resources, it is a key determinant of the degree to which their human needs are fulfilled. Some fields of work, such as music, can be described as unpropitious due to the unfavorable conditions awaiting skilled creators who seek to establish a full-time career; consequently, the human needs of such individuals may remain compromised. Alternative creativity is proposed as a type of meta-creativity that supports creative approaches to creative practice, and offers a new conceptual approach to careers in unpropitious creative fields. Alternative creativity provides hope for the many highly skilled musicians who exist in a state of perpetual career uncertainty, freeing them from the heavy burden of unrealistic expectations and the ensuing sense of failure that emerges when these expectations cannot be met. Ultimately, alternative creativity offers musicians the opportunity to reconceptualize and develop their creative practice while maintaining positive wellbeing through the fulfilment of their human needs.